Cryopreservation regimens of bone marrow mononuclear cells determine the formation of immune dendritic cells - Goltsev, Anatoliy; Gaevska, Yulia; Dubrava, Tetyana; Bondarovych, Mykola; Ostankov, Maksym (Problems of Cryobiology and Cryomedicine, 2025)
One of the innovative directions in the therapy of oncology diseases is the use of vaccines based on immune dendritic cells (iDCs). Th e paper presents the results of obtaining in vitro iDCs from bone marrow mononuclear cells (MNCs) cryopreserved under diff erent regimens using cryolysate of Ehrlich ascites carcinoma a cells. For the formation of iDCs, granulocytemacrophage colony-stimulating factor, interleukin-4 and cryolysate of Ehrlich ascites carcinoma cells were added to the culture medium as an inducer of dendritic cells (DCs) maturation. It was proven that immature DCs obtained from native or cryopreserved MNCs responded diff erently to the addition of inducers of iDCs formation. Th e cryolysate turned out to be a more potent inducer of iDCs than lipopolysaccharide, which was manifested by an increase in the expression level of all studied markers (CD11c, CD80, CD83, CD86). At the same time, the cryolysate maximally stimulated the expression of maturity markers (CD11c, CD83) on iDCs, which were formed from cryopreserved MNCs using regimens 1 at a rate of 1 deg / min to –80 °C with subsequent immersion in liquid nitrogen. Our fi ndings demonstrate the possibility of obtaining in vitro iDCs from MNCs cryopreserved under certain conditions using cryolysate of Ehrlich adenocarcinoma cells for further use in immunotherapy of oncology pathology. Probl Cryobiol Cryomed 2025; 35(1):23–32